The Scarcity of Specific Nutrients in Wild Bee Larval Food Negatively Influences Certain Life History Traits - Zuzanna M. Filipiak (Biology, 2020)
Bee nutrition studies have focused on food quantity rather than quality, and on details of bee biology rather than on the functioning of bees in ecosystems. Ecological stoichiometry has been proposed for studies on bee nutritional ecology as an ecosystem-oriented approach complementary to traditional approaches. It uses atomic ratios of chemical elements in foods and organisms as metrics to ask ecological questions. However, information is needed on the fitness effects of nutritional mismatches between bee demand and the supply of specific elements in food. We performed the first laboratory feeding experiment on the wild bee Osmia bicornis, investigating the impact of Na, K, and Zn scarcity in larval food on fitness-related life history traits (mortality, cocoon development, and imago body mass). We showed that bee fitness is shaped by chemical element availability in larval food; this effect may be sex-specific, where Na might influence female body mass, while Zn influences male mortality and body mass, and the trade-off between K allocation in cocoons and adults may influence cocoon and body development. These results elucidate the nutritional mechanisms underlying the nutritional ecology, behavioral ecology, and population functioning of bees within the context of nutrient cycling in the food web.